PERBEDAAN HASIL BELAJAR MATEMATIKA SISWA ANTARA YANG MENDAPATKAN MODEL PEMBELAJARAN BRAIN BASED LEARNING DENGAN NUMBERED HEAD TOGETHER - Wiwin Winarti; Cici Nurul Haq (Mosharafa: Jurnal Pendidikan Matematika, 2013)
Abstrak:The research was conducted to distinguish the two models , this is Brain Based Learning ( BBL ) with the Numbered Head Together ( NHT ) to see the extent to which the two models are instrumental in improving the learning outcomes of students learning mathematics . Authors wanted to see if there are differences in mathematics achievement between students who received  Brain Based Learning ( BBL ) with Numbered Head Together ( NHT ) ? . The method that I use in this study is experimental research that is giving treatment to two different classes . The population in this study were all  students class VII of SMP Negeri 1 Cikajang with a randomly selected sample of the class VII- C and class VII - D . The instrument used to measure student learning outcomes in the form mathematics objective tests , administered before and after the treatment the author gives a treat .  From the analysis of the Mann Whitney test , to test initial value Zhitung = 1.72 and Ztabel = 2.24 with a significance level of 5 % ( α = 0.05 ) zhitung  which is located in the reception area Ho , Ho is accepted then it means there is no difference initial ability between experimental classes experiment I and experiment II . While the results of Mann Whitney test to post test at significance level of 5 % ( α = 0.05 ) , zhitung = 3.18 using the two test sides of Zhitung value = 3.18 > Ztabel = 2.24 , in other words zhitung rejection of Ho is in the region , in other words Ha accepted . It means that there are differences in mathematics outcomes between students who received learning model with Brain Based Learning  (BBL) with Numbered Head Together (NHT).